Pengaruh Fasilitas Belajar Dan Lingkungan Keluarga Terhadap Motivasi Belajar IPA Peserta Didik Kelas VI Sekolah Dasar - Vinis Alvinia Waruwu; Mira Talina Telaumbanua; Kasiani Nazara; Yendri Julvan Telaumbanua; Yeremia Daeli; Analisman Lase; Yuniel Petrus Mendrofa; Lenan Juwita Harefa; Edward Harefa (Jurnal Riset Pendidikan Dasar (JRPD), 2024)
This article contains the influence of learning facilities and family environment on the learning motivation of science students in class VI elementary school. This research aims to determine (1) the influence of learning facilities on the learning motivation of science students in grade VI elementary schools, (2) the influence of the family environment on the learning motivation of science students in grade VI elementary schools, (3) the influence of learning facilities and the learning environment simultaneously on motivation studying science students in class VI elementary school. This research is a type of quantitative descriptive research, with a research sample of 78 students. Data collection techniques use questionnaires, documentation and interviews. The results of the research (1) there is a significant influence between learning facilities and learning motivation with a significance value of 0.004, (2) there is a significant influence between the family environment on learning motivation with a significance value of 0.000, (3) there is a simultaneous influence of learning facilities and the family environment towards learning motivation with a significance value of 0.000,